Adaptations of Presynaptic Dopamine Terminals Induced by Psychostimulant Self-Administration - Siciliano, Cody A. (ACS Chem Neurosci, 2014)
[Image: see text] A great deal of research has focused on investigating neurobiological alterations induced by chronic psychostimulant use in an effort to describe, understand, and treat the pathology of psychostimulant addiction. It has been known for several decades that dopamine neurotransmission in the nucleus accumbens is integrally involved in the selection and execution of motivated and goal-directed behaviors, and that psychostimulants act on this system to exert many of their effects. As such, a large body of work has focused on defining the consequences of psychostimulant use on dopamine signaling in the striatum as it relates to addictive behaviors. Here, we review presynaptic dopamine terminal alterations observed following self-administration of cocaine and amphetamine, as well as possible mechanisms by which these alterations occur and their impact on the progression of addiction.